An evaluation of the elementary science methods course at the University of San Carlos - Cagigas, Montana Ramos 1948-; University of San Carlos, Cebu City. (1973)
The methods course being offered to prospective elementary science teachers enrolled at the University of San Carlos was evaluated in this study.
Thesis (Master of Arts in Teaching)--University of the Philippines.
Keywords: Science -- study and teaching (Elementary) -- Philippines